2007
DOI: 10.3200/jach.55.5.261-266
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol's Effects on Women's Risk Detection in a Date-Rape Vignette

Abstract: Abstract.Researchers have established that alcohol is a risk factor for date rape for both victims and perpetrators. Objective: The authors tried to experimentally address the link between alcohol consumption and women's risk detection abilities in a risky sexual vignette. Participants: The authors recruited 42 women from undergraduate classrooms at a large midwestern university and randomly assigned them to drink an alcoholic (.04 blood alcohol content) or a placebo beverage. Methods: Participants completed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Colleges and universities need to be aware of the potential differential risk for problematic alcohol use in U.S.-born female Asian subgroup drinkers. Studies of general samples of college students have found that higher levels of alcohol consumption among women are often associated with greater risk of date rape, lower grade-point average, and marijuana and tobacco use (Loiselle and Fuqua, 2007;Vickers et al, 2004). The signifi cant fi nding of increased alcohol consumption among Asian subgroup college students who do not live with their parents is an important consideration for the development of college alcohol-intervention and prevention programs that target students' place of residence.…”
Section: Discussionmentioning
confidence: 99%
“…Colleges and universities need to be aware of the potential differential risk for problematic alcohol use in U.S.-born female Asian subgroup drinkers. Studies of general samples of college students have found that higher levels of alcohol consumption among women are often associated with greater risk of date rape, lower grade-point average, and marijuana and tobacco use (Loiselle and Fuqua, 2007;Vickers et al, 2004). The signifi cant fi nding of increased alcohol consumption among Asian subgroup college students who do not live with their parents is an important consideration for the development of college alcohol-intervention and prevention programs that target students' place of residence.…”
Section: Discussionmentioning
confidence: 99%
“…Initiators of a sexual advance may be less sensitive to body language and gestures intended to communicate that the overture is unwelcome when intoxicated (Abbey et al, 1998; Norris et al, 2002). Intoxicated target may be less able to communicate in a clear way that the overture is unwanted (Abbey et al, 2002) or recognize risks of sexual assault (Loiselle and Fuqua, 2007). Intoxication may also increase women’s likelihood of being targeted for sexual aggression (Ullman et al, 1999), perhaps partly because more intoxicated women are seen as being more sexually available (George et al, 1988; George et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Benson, Gohm, and Gross (2007) found that 78.7% of study participants reported alcohol use at the time of the assault. Even small amounts of alcohol affect college women's judgment of date rape risk (Loiselle & Fuqua, 2007).…”
mentioning
confidence: 99%